Does the Government’s Regulations in Land Ownership Empower the Protection of Human Rights? - Hariyanto, Hariyanto; Azizah, Mabarroh; Nurhidayatuloh, Nurhidayatuloh (Journal of Human Rights, Culture and Legal System, 2024)
Protection of land ownership has been regulated in various policies to protect human rights. However, it is essential to comprehensively examine the government's role in protecting land ownership because there are still various land conflicts. This research analyzes the government's role in protecting land ownership based on human rights principles and compares it with the Netherlands. This research uses a normative legal approach, using laws and cases and comparing policies with the policies of other countries. The research results show first, the Indonesian government guarantees the protection of land ownership through basic regulations on agrarian principles and the Indonesian government is trying to protect land ownership by registering land, limiting foreign land ownership, and developing governance plans at the regional level. Second, the Dutch government protects land ownership through a systematic, transparent land registration system implemented effectively to provide legal certainty for owners, investors, and related parties. Thirdly, Indonesia's regulatory approach adheres to the  basic regulations on agrarian principles  system, and the Netherlands uses civil law. However, both countries experience the same problems, such as land ownership disputes and scarcity. Therefore, the government needs to implement human rights-based policies through a transparent and fast land ownership process and public consultation in resolving land disputes.